Effects of empty fruit bunches application on oil palm root distribution, proliferation and nutrient uptake - Liew, Voon Kheong (2008)
Fertilizer losses due to environmental factors and doubt about the amount of fertilizers applied actually taken up by the palm increases the cost of Fresh Fruit Bunch (FFB) production. This study investigates the use of Empty Fruit Bunch (EFB) to better manage oil palm roots so that more nutrients from the applied fertilizers are absorbed rather than lost to the environment. The investigation studied the impact of EFB alone and supplemented with 0kg (N0), 1.5kg (N1) and 3kg (N2) of ammonium sulphate (AS), 0kg (K0), 1.5kg (K1) and 3kg (K2) of muriate of potash (MOP), and 0kg (P0) and 1kg (P1) of Christmas Island Rock Phosphate (CIRP) on root proliferation and soil chemical properties. Application of EFB alone increases roots mass and an increased in P, K, Ca and Mg levels in the soil. However, application of EFB supplemented with fertilizer combinations of N2P1 suppresses root proliferation while fertilizers at either N2 or P1 alone, encourage root proliferation when compared to control, N0P0. The study explored the importance of new roots in relation to older roots in absorbing nutrients. Isotopes 32P or 86Rb were used as tracers to study nutrient absorption by the roots. Results show that proliferation of new roots is important because the new roots, which are creamy white in color, were significantly (p < 0.05) more active in absorbing nutrients compared to older brown colored roots. The use of EFB with inorganic fertilizers to prolong root life span was also included in this study. Applying EFB with a supplement of AS and CIRP at 1.5kg/palm and 1kg/palm respectively, maintained root mass for a significantly longer period (p < 0.05) of six months compared to EFB with no fertilizer supplements. The impact of root loss on nutrient uptake was another aspect of this study. Roots were severed at 0, 25 and 50% of total root mass to simulate drought or other causes of root damage and the impact of such damage on nutrient uptake by the remaining living roots was determined. The rate of nutrient uptake by remaining surviving roots did not increase when 25 or 50% of roots were severed. However, removing 50% of root mass seems to impair the ability of the palm to produce more roots as indicated by the KN ratio in the frond. The KN ratio was significantly higher than control when 25% of roots were severed. The KN ratio was not significantly more (p > 0.05) than control when 50% of roots were severed suggesting the palms inability to adapt to the damage. The impact of increasing the amount of EFB applied was investigated. It was found that increasing the amount of EFB to more than 100kg/palm does not improve palm’s nutritional status particularly when its nutrient status is already at optimum. This study shows that application of 100kg EFB/palm supplemented with 1.5 kg AS/palm (N1) and 1 kg CIRP/palm (P1) can be used to increase the amount of new roots and to maintain them for six months. This finding is of much importance because it shows how fertilizer application and the subsequent nutrient acquisition by oil palm roots can be improved.